Firm expectations and economic activity - Enders, Zeno; Hünnekes, Franziska; Müller, Gernot J. (Working paper series, 2021)
We assess how firm expectations about future production impact current production and pricing decisions. Our analysis is based on a large survey of firms in the German manufacturing sector. To identify the causal effect of expectations, we rely on the timing of survey responses and match firms with the same fundamentals but different views about the future. Firms that expect their production to increase (decrease) in the future are 15 percentage points more (less) likely to raise current production and prices, compared to firms that expect no change in production. In a second step, we show that expectations also matter even if they turn out to be incorrect. Lastly, we aggregate expectation errors across firms and find that they account for about 15 percent of aggregate fluctuations.